Perkembangan Wakaf Asuransi Syariah di Indonesia Pasca Terbitnya Fatwa DSN-MUI No. l06 Tahun 2016 - Muh. Luthfi Hakim; Siti Asiyah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2020)
This research aims to explain how the development and potential of Waqf of Islamic insurance in Indonesia after published the fatwa by DSN-MUI in 2016 concerning the Waqf of insurance benefits and investment benefits in Islamic life insurance. This study uses a qualitative approach and use documentation methods as a data collection technique. All data will be analyzed by describing and making a general sense of the all data about the development of Waqf of Islamic insurance. The results of this research show that Waqf of Islamic insurance developed positively and has potential in the next future with a provision of conceptual and concrete constraints that can impede the development of Waqf of Islamic insurance can be responded to by the management of Waqf and public in general.